Developing Inclusive Preschool Education for Children with Autism Applying Universal Learning Design Strategy - Inese Tīģere; Dina Bethere; Pāvels Jurs; Velta Ļubkina (Education Sciences, 2025)
The study investigates the universal design for learning (UDL) framework, utilizing neuroscience-based principles to support all children, particularly those with autism spectrum disorder (ASD), within inclusive preschool environments. Highlighting the critical nature of early childhood for cognitive and social development, it examines practical UDL strategies implemented through a case study of five preschoolers, aged between 4 and 8 years, conducted from September 2023 to May 2024. The research employs observation aligned with UDL guidelines version 3.0., focusing on skill development in communication and social interaction. In the study, children’s skill development has been assessed using Vygotsky’s Zone of Proximal Development as the measurement framework. This concept underscores the importance of providing appropriate support and scaffolding to facilitate learning within a child’s optimal development zone. By integrating Vygotsky’s principles, the research highlights how tailored, supportive strategies—aligned with UDL’s emphasis on flexible, individualized support—can effectively bridge the gap between current abilities and potential, fostering meaningful skill acquisition and social growth. Findings affirm the effectiveness of UDL principles in facilitating inclusion and growth, emphasizing the importance of teacher competence in successful implementation.